2017
DOI: 10.1128/microbiolspec.funk-0056-2016
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Endosymbionts: Master Modulators of Fungal Phenotypes

Abstract: The ecological modes of fungi are shaped not only by their intrinsic features and the environment in which they occur, but also by their interactions with diverse microbes. Here we explore the ecological and genomic features of diverse bacterial endosymbionts-endohyphal bacteria-that together are emerging as major determinants of fungal phenotypes and plant-fungi interactions. We first provide a historical perspective on the study of endohyphal bacteria. We then propose a functional classification of three mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 145 publications
0
36
0
1
Order By: Relevance
“…A wide diversity of fungi harbor bacterial endosymbionts that influence fungal phenotypes related to growth, sporulation, and pathogenesis in plants. 94-98 Here we report for the first time a role for a bacterial endosymbiont in animals during infection with R. microsporus , a prevalent causative agent of fatal mucormycosis.…”
Section: Resultsmentioning
confidence: 84%
“…A wide diversity of fungi harbor bacterial endosymbionts that influence fungal phenotypes related to growth, sporulation, and pathogenesis in plants. 94-98 Here we report for the first time a role for a bacterial endosymbiont in animals during infection with R. microsporus , a prevalent causative agent of fatal mucormycosis.…”
Section: Resultsmentioning
confidence: 84%
“…The function of a specific microbe or microbial consortia is dynamic and depends on the developmental stage of the host, its age, reproductive state, or physiological condition (4)(5)(6). Several studies have recently found specific host-associated microbiota to contribute to host metabolism (7,8), development (9), organ morphogenesis (10), pathogen protection and immunity (11,12), behavior (13), environmental sensing and adaptation (5,(14)(15)(16)(17)(18)(19), developmental transitions (20)(21)(22)(23), and reproduction (24,25). Conversely, in the absence of a proper microbial community, the functioning of the metaorganism may be compromised, which can result in various diseases; in humans, for instance, anxiety, depression, diabetes, cancer, obesity, and chronic inflammations are linked to microbiome imbalances (6,26,27).…”
mentioning
confidence: 99%
“…Strains classified within the genus Luteibacter ( Gammaproteobacteria ) are yellow-pigmented members of microbiomes found in close association with plants (1–4). A subset of strains have also been characterized as endohyphal bacteria within a diverse set of ascomycete fungi (5–8). These bacterial/fungal complexes modulate diverse fungal phenotypes, including the potential for some fungi to act as plant growth promoters (5–8).…”
Section: Announcementmentioning
confidence: 99%
“…A subset of strains have also been characterized as endohyphal bacteria within a diverse set of ascomycete fungi (5–8). These bacterial/fungal complexes modulate diverse fungal phenotypes, including the potential for some fungi to act as plant growth promoters (5–8). To increase the amount of genomic information for strains in this genus, we have sequenced a species of Luteibacter originally isolated from rhizosphere soil of Pinus koraiensis (2).…”
Section: Announcementmentioning
confidence: 99%